Balancing nature conservation and windpower development: the contested work that maps do in protecting Europe's last wild reindeer. (17th February 2021) - Lundberg, Aase Kristine; Richardson, Tim
ABSTRACT: In conservation planning, maps do important work in producing territories of stronger and weaker protection, and spatially fixing special handling of development. Because of this, mapping and maps are contested, yet there have been few studies of their roles in planning conflicts. The performance of maps in planning processes affecting a wild reindeer habitat in Setesdal, Norway is analysed, asking what is the productive work of maps in planning, how is this work contested, and what are the consequences for the status of the plan itself. The case study centres on a proposal for wind power development, in an area designated in regional planning as a wild reindeer area of national significance. The analysis combines empirical material from interviews, planning documents and observation. The findings show the work that maps do in producing a new conservation territory, changing the basis of planning, yet failing to resolve deep-seated conflicts of interest.